Body mass index trajectories and noncommunicable diseases in women: The role of leisure time physical activity - Werneck, André O. [UNESP]; Oyeyemi, Adewale L.; Szwarcwald, Célia L.; Sardinha, Luís B.; Silva, Danilo R. (Wiley, 2020)
Objective: To analyze the association between body mass index trajectories and non-communicable diseases (NCDs) in women, and the interaction effects of leisure time physical activity on this relationship. Methods: Sample was composed by 15 628 women (≥30 years old) who performed objective measurement of body mass, height, and blood pressure in the 2013 Brazilian Health Survey (2013). Information regarding the body mass at 20 years old, current type 2 diabetes (T2DM), dyslipidemia diagnosis, and leisure time physical activity were self-reported by the participants. Socio-demographic and behavioral covariates were considered. Logistic regression models were used for the statistical analysis. Results: Those who were obese in both moments and women who become obese showed similar high risk, however, the prevalence of NCDs among women who were no longer obese was similar to the consistently non-obese. Leisure time physical activity attenuated the general deleterious effect of obesity, especially among the consistently obese women for dyslipidemia (inactive: OR: 2.02 [95%CI: 1.69-2.43] vs active: OR: 1.05 [95%CI: 0.55-1.99]), T2DM (inactive: OR: 3.84 [95%CI: 2.72-5.43] vs active: OR: 4.38 [95%CI: 1.49-12.86]) and high blood pressure (inactive: OR: 2.00 [95%CI: 1.56-2.57] vs active: OR: 1.15 [95%CI: 0.57-2.52]). Conclusions: Changes in body mass index appear to be sensitive to detecting the risk of NCDs over lifespan. In addition, leisure time physical activity attenuates the negative effects of obesity on NCDs, but this appears more important for the consistently non-obese women.